Cosmological implications of spectator and dynamical fields during inflation - JONATHAN HOLLAND (2020)
Some possible cosmological implications of the inclusion of spectator gauge ﬁelds in the inﬂationary action are considered. In this context, a spec-tator ﬁeld is a ﬁeld that is not directly responsible for inﬂation but can aﬀect cosmological observables. Spectator gauge ﬁelds can lead to novel and distinguishable features in inﬂationary models (as compared to single-ﬁeld inﬂation) that may be detectable. A model of anisotropic inﬂation is considered where universal anisotropy is maintained through a vector ﬁeld that is coupled to both the inﬂaton and its derivative. The derivative cou-pling reduces the anisotropy induced when compared to the non-derivative case, reducing tension with observations. SU(N) gauge ﬁelds appear natu-rally in the actions of string inﬂation models. The inclusion of an SU(N) gauge ﬁeld coupled both to scalars and pseudo-scalars (axions) is considered in two models of string inﬂation whose inﬂatons are K¨ahler moduli: K¨ahler moduli inﬂation and ﬁbre inﬂation. It is shown that the coupling between the axion and the gauge ﬁeld can lead to a large (chiral) enhancement of the tensor spectrum of these two models. In the case of K¨ahler moduli inﬂation, a model that generically predicts an unobservable value for the tensor-to-scalar ratio (r  10−3), this enhancement is capable of boost-ing the tensor-to-scalar ratio to values that will be potentially observable at next generation detectors. However, the parameters required to achieve this goal may present a challenge for its successful realisation in string theory. In the case of ﬁbre inﬂation, a model that generically predicts an observable value for the tensor-to-scalar ratio, it is shown that this enhancement can render the tensor spectrum of ﬁbre inﬂation almost entirely chiral, giving it a distinguishable feature that may be detectable.